ANALISIS POTENSI PERTANIAN TANAMAN JAGUNG DESA PADENGO KECAMATAN DENGILO BERBASIS SISTEM INFORMASI GEOGRAFI (SIG) - Hasan, Hais; Kurniawati, Nevi; Ramadhani, Bulan Suci; Lodjo, Liberty (SULIWA: Jurnal Multidisiplin Teknik, Sains, Pendidikan dan Teknologi, 2025)
Geographic information system (GIS) is a technology that is currently a very important tool in storing, manipulating, analyzing and displaying natural conditions with the help of attribute data and spatial data that can be visualized. The purpose of this study is: To determine the potential suitability of agricultural land based on Geographic Information System (GIS) Method: used in this study is a qualitative approach method. Results: this study is land suitability using ArcGIS 10.3 software, there are 31.65 ha for land not suitable for corn commodities and 228.94 ha are classified as "suitable" while 574.70 ha are classified as "quite suitable". Each of these areas is found in each hamlet area in the research location, namely Padengo Village, Dengilo District.